The Radio Imaging Method (RIM) -- A Means Of Detecting And Imaging Anomalous Geologic Structures In A Coal Seam - Rodger Fry (International Conference on Ground Control in Mining, 1984)
All coal deposits contain anomalous geologic conditions which have an impact on roof control, Run-Of--Mine (ROM) coal quality and production costs. To remain competitive in today's coal market and provide a safe working atmosphere, mine operators need to know in advance of mining the geologic conditions which prevail in the coal deposit. In order to identify geologic anomalies within a coal seam and surrounding roof rock in advance of mining, the Radio Imaging Method (RIM) survey procedure has been developed. This paper describes the RIM procedure and how it is used to predict various geologic conditions within a coal deposit. Figure 1 illustrates the RIM in-mine and surface surveys which can be used in an underground mine. [ ] RIM is an electromagnetic (EM} wave process which consists of in-mine and surface survey techniques. Both techniques are used in underground coal mines to detect faults, interbedding, sandstone channels, and thinning coal. Thesurface survey can also be used to determine seam correlation and continuity in strip and underground mining. In-mine and surface surveys work by propagating EM waves along straight paths through the coal. As the RIM signal travels along a ray path, it interacts with the seam material and surrounding rock. This interaction causes the signal to lose energy thereby decreasing its strength along the path. The amount of energy loss per unit path length depends upon the coal seam height and type of surrounding roof and floor rock. A reading of the signal level is taken at the end of the ray path at the receiver location. This reading is used to determine the loss (attenuation) rate of the signal along the path. The signal level data is compiled and analyzed through computerized algorithms which construct images of any anomaly present. This graphical depiction of the coal provides a basis for further geologic interpretation. By comparing the images reconstructed by the RIM analysis to in-mine geologic mappings made while mining through RIM study zones, it has been confirmed that RIM can help detect the following; Rapidly Thinning Coal Incompetent Roof Rock Poor Floor Lithology